STUDIES ON THE PERMEABILITY OF SOME TYPICAL SOIL PROFILES OF RAJASTHAN IN RELATION TO THEIR PORE SIZE DISTRIBUTION AND MECHANICAL COMPOSITION - Singh, K S; Singh, Goverdhan (Annals of Arid Zone, 2016)
Permeability, pore size distribution and mechanical composition of some profiles of Rajasthan were determined. The permeabilily of the soil profiles in general decreased down wards. The coefficient of permeability of Dungargarh soil was highest and of Kota was lowest at all the depths. e capillary porosity and silt plus clay content of the soil samples were negatively correlated, whereas. non-capillary porosity total pores pace and sand content were positively correlated with the coefficient of permeability. Capillary porosity. silt plus clay per cent, non-capillary porosity and sand percent had significant correlation with the permeability. The relationship between coefficient of permeability and per cent total porespace was not significant.